Petersen's Hernia. Is it a Calculated Risk? - Yamileth, Jiménez Bonola; Adolfo, García Sánchez Morelos; Mireya, De La Fuente González; Isabel, Estrada Rodríguez María; Israel, Flores Pazos Mauricio; Antonio, García Díaz Edson; Enrique, Shafler Tenorio; Antonio, De Luna Berrones; Sofía, Hernández Medina Myrna (British Journal of Healthcare and Medical Research, 2023)
Hernias as a pathological entity in Surgery are very frequent; while Petersen's hernia is a complication acquired after abdominal surgery independently in any type of digestive anastomosis. The objective is to report a case and carry out a review of the literature. A 47-year-old female with G III obesity, 4 years ago justified bariatric surgery of the Roux-en-Y gastric bypass by laparoscopy, with data of intestinal occlusion and acute abdomen. An emergency exploratory laparotomy was performed, finding Petersen's internal hernia, with reduction without complications with a satisfactory evolution. Petersen's hernia as a practically exclusive complication of Bariatric Surgery has been increasing exponentially in terms of its incidence in recent years, due to the reintroduction of the laparoscopic approach. The difficulty of an early diagnosis causes catastrophic complications, so a delay in the diagnosis, decision and surgical management, has devastating consequences. In terms of surgery, it is a challenge for the medical professional that requires exquisite preparation, character, iron and strict discipline. That is why an omission, an error, a bad decision has catastrophic consequences. And an example of this is Petersen's hernia, as an acquired pathology secondary to a calculated omission or error by the surgeon in the surgical technique, more than costing financial, human resources or the patient's life itself.